AN OPEN-LABEL RANDOMIZED CLINICAL STUDY OF TOPICAL NANOPARTICULATE ANTIPSORIATIC POLYHERBAL CREAM - BHISE, KIRAN; MULLA, GHAZALA; SHAIKH, SHAHEEN; ZIYA-UL-HAQ-CHOWDHARY; KHAN, SHADAB (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Objective of the study was to investigate the safety, efficacy, and antipsoriatic activity of topical cream enriched with Nanostructured Lipid Carriers (NLC) of Azadirachta indica, Lawsonia inermis, and Mallotus philippensis through the controlled clinical study. Methods: The randomized controlled trial was performed for 12 months on 65 adult patients between the age group 20 and 60 years of either sex of diagnosed, uncomplicated cases of psoriasis Vulgaris. The Test group received a local application of the herbal antipsoriatic NLC enriched cream, while the Control group was treated with Clobetasol propionate 0.05% cream twice daily for 3 months. Both groups were assessed for parameters of skin and nail examinations, lab investigation, and Psoriasis Area and Severity Index (PASI) score. The data were analyzed and interpreted statistically. Results: Significant improvement in itching and PASI score was seen during successive visits in both groups. However, recurrence of mild itching and erythema in a few patients of the control group was seen after 2 weeks, whereas no such recurrence is seen in the test group. Statistically significant reduction in eosinophilia in the control group was observed before and after treatment. The efficacy of clobetasol in the control group and the prepared formulation in the test group both show statistical efficacy at par. Conclusion: The data suggest that the NLC enriched cream exhibited significant relief in all the symptoms of psoriasis and therefore can be used as a potent antipsoriatic agent due to the easy availability of the drugs and cultural affinity for herbal formulations.